FAKTOR–FAKTOR YANG BERHUBUNGAN DENGAN PENCAPAIAN PERKEMBANGAN MOTORIK KASAR PADA BALITA (1-5 TAHUN) DI PAUD MENARA ILMU LIMBOTO - Andi Akifa Sudirman; Euis Hidayat (-, 2021)
This research conducted to determine the factors correlated with task achievement of toddlers (1-5 years) ‘s gross motorist development at PAUD Menara Ilmu Limboto of Gorontalo Regency by used indicators of nutritional status, parenting, and the role of the teacher. This research is observational with cross sectional study. The population in this study all infacts (1-5 years) amounted to 76 people. Collection of the data used questionnaires, while techniques of data analysis used Chi Square test. The result showed that the nutritional sttus, parenting, and the role of the teacher are very influential on the toddlers’ gross motorist development. Based on bivariate analysis used the chi-square test, P values α 0,05 is for the environment with the behavior of P= 0,000